EKSPERIMEN PEMBUATAN SATE TAICHAN KUAH TONGSENG - Puput Dewi Anggraeni (Journal of Hospitality and Tourism, 2023)
Satay is one of the mainstays of Indonesian cuisine which has more than one type, such as Madura satay, Padang satay, Klatak satay, and other types of satay. One of the satays that is currently in great demand is "Taichan satay" and this is a business opportunity that is quite popular today. Sataytaichan began to grow rapidly since 2016 until now.This study is an experimental study that aims to determine the manufacturing process in taichan satay with tongseng sauce. In this study, Taichan satay is modified with Tongseng sauce. Tongsengis a traditional Indonesian culinary that is processed by roasting spices with soy sauce combined with curry sauce.The cooking method used in this study is roasting the satay and then using the boiled method to make the tongseng sauce. This study used organoleptic test analysis and hypothesis testing and then processed using SPSS (Statistical Product and Service Solutions) tools. The results in this study indicate that the results of the significant value of Taste 0.089, Texture 0.673, Color 0.696, Aroma 0.696 are accepted.tools. The results in this study indicate that the results of the significant value of Taste 0.089, Keyword: Taichan Sate, Tongseng Sauce, roasting and Boiled Techniq